2(b+1)-(9+b)=-6

Simple and best practice solution for 2(b+1)-(9+b)=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(b+1)-(9+b)=-6 equation:


Simplifying
2(b + 1) + -1(9 + b) = -6

Reorder the terms:
2(1 + b) + -1(9 + b) = -6
(1 * 2 + b * 2) + -1(9 + b) = -6
(2 + 2b) + -1(9 + b) = -6
2 + 2b + (9 * -1 + b * -1) = -6
2 + 2b + (-9 + -1b) = -6

Reorder the terms:
2 + -9 + 2b + -1b = -6

Combine like terms: 2 + -9 = -7
-7 + 2b + -1b = -6

Combine like terms: 2b + -1b = 1b
-7 + 1b = -6

Solving
-7 + 1b = -6

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + 1b = -6 + 7

Combine like terms: -7 + 7 = 0
0 + 1b = -6 + 7
1b = -6 + 7

Combine like terms: -6 + 7 = 1
1b = 1

Divide each side by '1'.
b = 1

Simplifying
b = 1

See similar equations:

| -3v-4v=14 | | 0.8m+2.6=0.2 | | ln(x+3)=2ln^4 | | 3+(-1/2) | | 9.54=p | | 2(3m+8)=2 | | 9(d-7)=81 | | -c/3-20=0 | | 9(d-7)=8 | | -2+(-1/2) | | .5x+1=1.5 | | 5x+8=4x+4 | | 9x+82=1 | | 2y-14=7+7y | | 5x^2-30x-12=y | | =0.8571428571+0.4285714286y | | 7x=3y+6 | | -1/2+(-2) | | 2q-3=27 | | x^2+25x+10=0 | | n+6.3= | | (4y+4)-(2+3y)=9 | | -1/2+2 | | 1/4/9/8 | | 1/2*1 | | 3m-9=15 | | 3x-1=8x+2 | | -23+10=3x+5-2x | | 4(3b-2)=5(2b+4) | | 10x+2(2-x)=8x+4 | | -4(x+3)-41=1-34 | | 4x+(x-1)=19 |

Equations solver categories